Pengaruh Disiplin Pegawai, Kepemimpinan dan Lingkungan Kerja terhadap Kinerja Pegawai dengan Kepuasan Kerja sebagai Variabel Mediasi pada Kantor Kecamatan Maulafa Kota Kupang - Peuuma, Maria Katarina Umiti; Perseveranda, M. E.; Manafe, Henny A.; Man, Stanis; Bibiana, Rere Paulina (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the influence of leadership, work environment and job satisfaction variables on employee performance at the Maulafa District Office, and the ability of job satisfaction variables to mediate the influence of work discipline, leadership and work environment on the performance of Maulafa District Office employees. The quantitative approach used in this research, while the sample consisted of 37 employees of the Maulafa District Office. Questionnaires were used to collect data, which was then analyzed using the SmartPLS program and descriptive and inferential statistics. The research results show that work discipline, leadership, and work environment have a significant influence on employee job satisfaction. This also shows a significant influence on employee performance, with job satisfaction mediating the influence of leadership and work environment on employee performance compared to job satisfaction mediating the influence of work discipline on employee performance.